Animal Law Syllabus Design: A New Zealand Perspective - M.B. Rodriguez Ferrere (Legal Education Review)
Islamic Shari’ah forms the basis of laws in KSA. The Islamic provisions are considered as supreme over the codified laws and direct the state’s regulations. A close review of the Saudi legal system makes it apparent that it follows both the written and unwritten laws. Because the Shari’ah is considered as the state’s supreme law and cannot be overridden by the codified laws. This study has taken into account the given principle and makes recommendations as for how the curriculum can be redesigned to improve the capabilities of prospective professionals regarding integrating the different law components with the fundamentals of Shari’ah law. The study examines degree plans in KSA universities; most of these offer mandatory Islamic law courses. The adequacy of these courses, however, remains questionable as for whether these apply to the comprehensive provisions of Islamic law or not. Results suggest that courses must be offered which allow students to not only develop stronger foundations in general, but also enable them to better integrate the non-codified rules of law with the Islamic law.